Extracellular protease-producing actinomycetes and other bacteria in cultivated soil - Raina Niskanen (Agricultural and Food Science, 1986)

(untitled)
The occurrence and properties of extracellular protease-producing actinomycetes and other bacteria in cultivated soil were studied. Experimental soils consisted of three mineral soil samples and one Sphagnum peat sample from a greenhouse. The mineral soil samples represented arable, pasture and uncultivated soils. From experimental soils, 240 bacterial strains were isolated, 68 strains there of were proteolytic. A greater number of proteolytic strains originated from pasture soil than from the other soils. Actinomycetes accounted for 70 % of the proteolytic strains isolated from pasture soil. Several proteolytic bacteria were isolated also from peat, but only few of them were typical actinomycetes. Many strains with high extracellular protease activity proved to be fermentative bacilli. Production of oxidase enzymes, significant in the humification processes, occurred frequently among strains isolated from pasture soil and peat. The ability to produce dark melanoid pigments was a frequently noted characteristic of the proteolytic actinomycetes.